Nature and nurture: a case of transcending haematological pre‐malignancies in a pair of monozygotic twins adding possible clues on the pathogenesis of B‐cell proliferations. (5th March 2015) - Hansen, Marcus C.; Nyvold, Charlotte G.; Roug, Anne S.; Kjeldsen, Eigil; Villesen, Palle; Nederby, Line; Hokland, Peter
Summary We describe a comprehensive molecular analysis of a pair of monozygotic twins, who came to our attention when one experienced amaurosis fugax and was diagnosed with JAK2+ polycythaemia vera. He (Twin A) was also found to have an asymptomatic B‐cell chronic lymphocytic leukaemia (B‐CLL). Although JAK2−, Twin B was subsequently shown to have a benign monoclonal B‐cell lymphocytosis (MBL). Flow cytometric and molecular analyses of the B‐cell compartments revealed different immunoglobulin light and heavy chain usage in each twin. We hypothesized that whole exome sequencing could help delineating the pattern of germline B‐cell disorder susceptibility and reveal somatic mutations potentially contributing to the differential patterns of pre‐malignancy. Comparing bone marrow cells and T cells and employing in‐house engineered integrative analysis, we found aberrations in Twin A consistent with a myeloid neoplasm, i.e. in TET2, RUNX1, PLCB1 and ELF4. Employing the method for detecting high‐ranking variants by extensive annotation and relevance scoring, we also identified shared germline variants in genes of proteins interacting with B‐cell receptor signalling mediators and the WNT‐pathway, including IRF8, PTPRO, BCL9L, SIT1 and SIRPB1, all with possible implications in B‐cell proliferation. Similar patterns of IGHV‐gene usage to those demonstrated here have been observed in inherited acute lymphoblastic leukaemia. Collectively, these findings may help in facilitating identification of putative master gene(s) involved in B‐cell proliferations in general and MBL and B‐CLL in particular.